Enabling Best Practices for Cardiac Radioablation Through a Remote Education and Peer Review Program - Robinson, C.G.; Hugo, G.D.; Moore, K.M.S.; Samson, P.; Contreras, C.; Cooper, D.H.; Cuculich, P. (International journal of radiation oncology, biology, physics, 2021)
Noninvasive cardiac radioablation (CRA) is increasingly used for treatment of high-risk ventricular tachycardia (VT). In an effort to promote consistency and disseminate best practices learned from our experience and that of other centers, we developed a remote education and peer review program via our Center for Noninvasive Cardiac Radioablation (CNCR). We report structure and international engagement via the CNCR program. Centers that contacted CNCR with interest in starting a CRA program were provided with a digital packet of relevant literature on CRA, as well as brief guidance documents for optimizing simulation, image reorientation, and targeting. An introductory video call was scheduled with representatives from electrophysiology and radiation oncology between the site and CNCR. A consistent set of topics was discussed with each center in light of their local capabilities, including general principles of patient selection, targeting, simulation, motion management, treatment planning, delivery, and follow-up, and when appropriate, regulatory and billing issues. To facilitate consistent approaches to discussion of targeting, the American Heart Association 17-segment model construct was employed. For centers with a potential CRA case(s), interactive peer review was accomplished for targeting and planning, with the final decision for treatment at the discretion of the treating centers. From 2019 to present, 50 centers have engaged with CNCR through our program, representing 11 countries across 5 continents. Following initial engagement, 35/50 (70%) have treated at least one patient (range, 1-7), with 82 patients treated to date. Ninety-seven percent (34/35) of centers have maintained active engagement with CNCR following initial treatment of their first patient. Subsequently, three of those centers have develop prospective IDE trials through the FDA. All centers have committed to engagement in a newly established international registry and enrollment on developing clinical trials. Cardiac radioablation is undergoing rapid uptake as a potential treatment for patients with high-risk VT, with the potential for wide variability in implementation. The CNCR remote education and peer review program has enabled rapid engagement with centers around the world, with a focus on best practices, establishing relationships for mutual sharing and collaboration, and encouraging prospective evaluation of safety and efficacy for CRA.